Value Relevance of Financial Performance Measures: An Empirical Study - Almagtome, Akeel Hamza; Abbas, Zahraa Fadhil (International Journal of Psychosocial Rehabilitation, 2020)
Accounting literature shows that the elements of the financial statements have different effects on the value of the company in the financial market and on the behavior of the investors in the financial market. The aim of this paper is to test the relevance of the value of financial performance metrics that can provide investors with useful information on the assessment of corporate performance. In this study, three financial performance measures are used, i.e. operating income, total revenue and dividend, to show its relationship to market indicators, both stock prices and total traded shares. It uses financial data for a sample of 33 banks registered on the Iraqi Stock Exchange for a period of 8 years (2010-2017) with a total of 264 observations. The results show that the indicators of operating income, total revenues and dividends are value-relevant information. The results of the comparison between the financial performance measures show that the correlation between the operating income index and the stock prices as well as the total traded stocks was higher than the other performance indicators (total revenue and dividends). The results of this study support capital markets by providing a better understanding of the importance of the different financial performance measures for investors and the extent to which they reflect on stock prices.